On the Issue of the Discriminatory Nature of an Aggravating Criminal Punishment Circumstance in the Form of an Intentional Crime by an Employee of the Internal Affairs Body - R. Sh. Urazbaev (Сибирское юридическое обозрение, 2020)
The paper analyses the aggravating circumstance provided by item “o” of part 1 of Article 63 of the Criminal Code of the Russian Federation. It proves that this law norm is discriminative on the basis of profession. The paper demonstrates that the aggravating circumstance is inconsistent with several principles of the criminal law, namely principle of justice, principle of humanity, and constitutional principle of equality of all before the law, and that application of the aggravating circumstance involves violation of the listed principles. The Author provides a review of a definition given by the Constitutional Court of the Russian Federation considering the analyzed criminal law norm.